2023
DOI: 10.1002/adfm.202302136
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Liquid‐Liquid Phase Separation Induces Tunable Anisotropic Nanocrystal Growth for Multidimensional Analysis

Abstract: Spatially directed biomineralization of nanocrystals for specific optical purposes in biological systems and elucidation of the mechanism of biomineralized nanocrystals remains a fascinating but extremely challenging task. Herein, the biomineralization of tunable gold nanocrystals with in situ protein coronas by intracellular liquid‐liquid phase separation (LLPS) for in situ molecule surface‐enhanced Raman spectrum (SERS) analysis and tumor fluorescence identification. The anisotropic nanocrystals are realized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The specific mechanisms of the metabolic conversion of Au 3+ to Au 0 are not well established; however, a number of previous studies indicated the involvement of ROS/RNS, , , NADH dehydrogenase flavoprotein 2 and quinone oxidoreductase-like protein, and glutamate, as well as several proteins that bind cations, energetic metabolites, or nucleotides. ,, If the formation of GNPs from gold ions were to disrupt the relative abundance of those biomolecules, this could enhance radiosensitization, complementing the sensitization afforded by the intracellular biosynthesis of gold particles. To explore the hypothesis that GNC biomineralization could enhance radiosensitization by modulating cancer cell metabolism and also to uncover potential biological mechanisms of gold biomineralization, we treated PANC1 cells with Au 3+ without radiation using untreated cells as a control and performed global metabolomic and lipidomic profiling using ultrahigh pressure liquid chromatography coupled to ultrahigh resolution mass spectrometry (UHPLC-HRMS).…”
Section: Resultsmentioning
confidence: 99%
“…The specific mechanisms of the metabolic conversion of Au 3+ to Au 0 are not well established; however, a number of previous studies indicated the involvement of ROS/RNS, , , NADH dehydrogenase flavoprotein 2 and quinone oxidoreductase-like protein, and glutamate, as well as several proteins that bind cations, energetic metabolites, or nucleotides. ,, If the formation of GNPs from gold ions were to disrupt the relative abundance of those biomolecules, this could enhance radiosensitization, complementing the sensitization afforded by the intracellular biosynthesis of gold particles. To explore the hypothesis that GNC biomineralization could enhance radiosensitization by modulating cancer cell metabolism and also to uncover potential biological mechanisms of gold biomineralization, we treated PANC1 cells with Au 3+ without radiation using untreated cells as a control and performed global metabolomic and lipidomic profiling using ultrahigh pressure liquid chromatography coupled to ultrahigh resolution mass spectrometry (UHPLC-HRMS).…”
Section: Resultsmentioning
confidence: 99%
“…We further analyzed the mechanism of CDs@SiO 2 -based teeth whitening using Raman spectroscopy, a molecular analytic tool with unparalleled advantages in biomineralization analysis due to its ability to obtain the vibrational peaks of chemical bonds in substances. The characteristic marked bands of the Raman spectra of enamel at 1003, 1031, 1258, 1450, and 1665 cm –1 correspond to phenylalanine, amide III, CH 2 , and CH 3 deformations and amide, respectively. , The characteristic bands of minerals at 430, 585, 960, and 1070 cm –1 in the Raman spectra can be assigned to ν 2 PO 4 3– , ν 4 PO 4 3– , ν 1 PO 4 3– , and ν 1 CO 3 2– , respectively. The enamel surface before and after treatment with PBS showed no obvious characteristic peaks of biomineralization, probably due to the fluorescence peaks of contaminants (Figure a,b). The ν 1 PO 4 3– (960 cm –1 ) vibrational peak is the most abundant component of the enamel and is the characteristic peak of hydroxyapatite .…”
Section: Resultsmentioning
confidence: 99%
“…39−41 The characteristic marked bands of the Raman spectra of enamel at 1003, 1031, 1258, 1450, and 1665 cm −1 correspond to phenylalanine, amide III, CH 2 , and CH 3 deformations and amide, respectively. 42,43 The characteristic bands of minerals at 430, 585, 960, and 1070 cm −1 in the Raman spectra can be assigned to ν 2 PO 4 , respectively. 44−47 The enamel surface before and after treatment with PBS showed no obvious characteristic peaks of biomineralization, probably due to the fluorescence peaks of contaminants (Figure 4a,b).…”
mentioning
confidence: 99%
“…Importantly, the protein corona can be analyzed in the original biological environment without interference by extraction and separation steps. Many techniques have already been employed to study the protein corona in situ, such as nuclear magnetic resonance, 36 sum frequency generation, 37 surface-enhanced Raman spectroscopy, 38 and synchrotron-radiation circular dichroism. 39 However, in situ investigation of the protein corona directly at the in vivo level is still inadequate.…”
Section: Protein−nanoparticle Interactionsmentioning
confidence: 99%